Maize in Zambia: Effects of technological change on food consumption and nutrition - Kumar, Shubh K.; Siandwaze, Catherine (International Food Policy Research Institute, 1994)
This chapter examines household food consumption patterns and nutrition status of the population in Easter Province, Zambia, as well as the effects of adoption of new maize technologies on their characteristics.